Optimasi Sterilisasi Minuman Jamu Kunyit-Asam Kemasan dengan Metode Pasteurisasi - Putri, Meilani; Syuhada, Syuhada; Rukaya, Benazir Evita (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to evaluate the effect of pasteurization at 65Â°C and 85Â°C on pH stability, organoleptic characteristics, and microbiological contamination of turmeric and tamarind herbal medicine during 15 days of storage. This research is an experimental study in the laboratory. The research methods include pasteurization at the two temperatures, pH testing, organoleptic tests (including colour, aroma, and taste), and total plate count (TPC) analysis to assess microbial contamination. The results of the study showed several main findings (1) pasteurization was effective in maintaining the stability of pH, colour, and aroma of turmeric and tamarind herbal medicine during 15 days of storage; (2) there was an increase in flavour intensity on the 15th day in the pasteurized group; (3) pasteurization at 85Â°C reduced the lowest microbial contamination rate (1.85 Ã— 10Â¹â° CFU/mL) compared to the group without pasteurization (3.33 Ã— 10Â¹â° CFU/mL). Thus, pasteurization in this study increased microbiological safety and affected the sensory characteristics of turmeric and tamarind herbal medicine, especially in taste intensity.